Aquaponics farming method as a solution for sustainable food security / Ahmad Faiz Ab Nasir ... [et al.] - Ab Nasir, Ahmad Faiz; Weller, Maike; Mohd Fazil, Nur Aliyah; Ramli, Suriana (2022)
Aquaponics has quickly become a well-known solution for sustainable food production. The term "aquaponics" is made up of hydroponics and aquaculture and was first used in the 1970s. It is a production system that is innovative and intelligent, a method that integrates aquaculture (fish production) with hydroponics (plant production in water without soil). It plays a significant role in the future of environmental and socio-economic sustainability, especially in highly developed urban areas, by reducing city waste and improving urban biodiversity and air quality. In other words, it contributes to ensuring food security for the urban community through enabling local, fresh, pesticide-free, and healthy production with short supply chains in cities. Due to this fact, aquaponics meets several objectives of sustainable development, and it is the best option to apply as an urban farming method. Currently, Malaysia is emphasizing agriculture due to food insecurity as well as the traditional farming system, climate change, and environmental agenda. Since aquaponics can contribute to environmental and socio-economic sustainability, several objectives have been developed for this project. The first objective is to provide a workable and affordable aquaponics method of implementation in a small or confined place so that it can be used by residents in the apartments. The successful implementation of aquaponics can have a positive impact on the environment, economy, and society. It is also hoped to provide a circular economy that would sustain the business and make it profitable to the society in the long term. The second objective of this project is to enhance food security and ensure sustainable food production is applied when implementing the aquaponics system, as it can be used to improve the livelihoods of households and communities. To achieve the project objectives, firstly, there is a need to develop strategies focused on raising awareness of the aquaponics system among Malaysians. This can be materialized through collaborative governance that takes into consideration the contributions of government and the private sectors. Next, a continuous training and up-skilling program needs to be introduced to generate more knowledge and enhance the participants' skills. This training would be able to develop value-added marketing skills among the participants and increase their ability to apply circular economy principles to their projects. It is crucial for the participants to have knowledge of fish, bacteria, and plant production in order for the implementation to be successful. To conclude, the aquaponics system is very sustainable and environmentally friendly to be applied in urban areas. The urban community sees it as an economically oriented way to operate as their supplier of food, and the impact would reduce their household cost of living.